(untitled) (Bangladesh Journal of Child Health, 2018)
Background: In malaria endemic areas diagnosis of severe malaria by microscopy and immunodiagnostic test is confounded by asymptomatic peripheral blood parasitemia. In such settings, retinal changes by ophthalmoscopy showed some diagnostic utility. Contribution of ophthalmoscopy in diagnosis of severe malaria in children is not well studied in Bangladesh. The aim of this study was to describe the retinal findings in children of cerebral and non-cerebral severe malaria by direct and indirect ophthalmoscope and relate their outcome and to determine the course of changes in the fundus. Methodology: In this prospective observational study 130 consecutive children aged between 6 months to 12 years admitted with confirmed severe Plasmodium falciparum malaria in pediatrics ward of Chittagong Medical College Hospital, Chittagong, Bangladesh were assessed by both direct and indirect ophthalmoscopy during the period of April 2008 to March 2009. Results: Out of 130 patients 80 children had cerebral malaria and of these 49 (61.2%) had some degree of retinopathy; 24 (48%) of 50 with non cerebral severe malaria had retinopathy. Predominant retinal changes were Retinal hemorrhage and Macular whitening each in 53 (40.77%) patients, followed by peripheral whitening, Vessels changes and papilloedema in 50 (38.46%), 40 (30.77%) and 14 (10.78%) patients respectively. With indirect ophthalmoscope as reference, direct ophthalmoscopy had a high sensitivity to detect macular whitening, and papilloedema but was less sensitive to detect peripheral whitening and vessel changes. Patients with retinopathy had more chance to had unfavorable outcome (Death) in comparison to the patients who had not Odds ratio:1.09 (95% CI:1.017-1.167). Most of these retinal changes were transient and resolved gradually as clinical condition improved. Conclusion:Features compatible with malarial retinopathy were commonly found in our children with severe malaria. Ophthalmoscopy is an important clinical tool to aid in diagnosis and prognosis in children. However, indirect ophthalmoscopy provides better information than direct ophthalmoscopy. Bangladesh J Child Health 2018; VOL 42 (3) :118-124